The Routledge Research Companion to the History of Evangelicalism. Edited by Andrew Atherstone and David Ceri Jones - Buchanan, Colin O. (The journal of theological studies, 2020)
This ‘Companion’ is what it says on the cover, a companion. It is not itself a history, and it has little overall picture of an unfolding and growing organic movement. Rather, it identifies some characteristic features of evangelicalism, and traces the story of each of these seriatim. The scope is in theory five centuries of time and the whole globe in space. The upshot brings certain trees into sharp focus without giving very much picture of either the wood or the neighbouring trees. The reader’s interest is directed to these particular concerns—some very general and predictable (as, e.g., ‘Evangelicals and the Bible’), some much less expected (as, e.g., ‘Evangelicals, money and business’).